Competencies for food graduate careers - Weston, Emma (2019)
Food sciences-based technical graduates are a significant proportion of the food and drink industry’s intake. Unlike many other graduate career pathways in the UK, aside from technical standards, there is no cohesive food science competency framework to support the key stakeholders of employers, students and degree providers. Clarity of desirable competencies for the range of graduate opportunities available, would enable students to undertake effective career planning and personal development, and educators to refine programmes to satisfy market needs. This study aimed to develop a competency framework using a mixed methods approach. By engagement of a stakeholder group, an initial language tool was developed by a series of semi-structured interviews, followed by thematic analysis and group consolidation using a modified-Delphi approach. Steps to increase confidence in validity included student group interviews at three universities. After identification of typical graduate roles, the new language tool was incorporated into an industry-wide online survey (UK and Republic of Ireland), evaluated by descriptive analysis and principal component analysis. The tailored competency framework, Competencies for Food Graduate Careers (CFGC), is a set of 48 elements outlining which are desirable for each of 14 typical graduate roles. Following development of appropriate methodology, CFGC was mapped against food sciences curricula at University of Nottingham (UoN) to evaluate appropriate levels of inclusion of each element in degree programmes. Initial integration of CFGC for careers education of UoN undergraduate students has been successful. Online resources have been developed to complement direct use at UoN, and support wider access to CFGC. To increase the quantity of ‘oven-ready’ graduates entering the food industry, it is recommended CFGC be used for careers education and competency development by other degree providers. It can also underpin national initiatives already begun to encourage young people to enter the food industry as career.